FoxP3− Tr1 Cell in Generalized Myasthenia Gravis and Its Relationship With the Anti-AChR Antibody and Immunomodulatory Cytokines - Meng, Huanyu; Zheng, Shuyu; Zhou, Qinming; Gao, Yining; Ni, You; Liang, Huafeng; Chen, Sheng (Frontiers in Neurology, 2021)
Introduction: The changes in the number and function of regulatory T cells (Tregs) are thought to play important roles in the pathogenesis of generalized myasthenia gravis (gMG). Previous studies have suggested the decrease of FoxP3+ Treg cells in the MG development. However, there is no study on the pathophysiological mechanism of FoxP3−Treg, especially Tr1 cells, in gMG patients. Therefore, this study was conducted to reveal the effect of Tr1 cells to the pathophysiology of gMG. Methods: Thirteen patients with gMG and twelve healthy volunteers were enrolled in this study. The titer of anti-AChR Ab was measured by ELISA. The separated PBMCs were labeled for CD4, CD25, CD49b, LAG3 and FoxP3. The CD4+ T cell count, FoxP3+ Treg to CD4+ T cell ratio and Tr1 cell to CD4+ T cell ratio were measured by flow cytometry. Based on the FoxP3+ Treg and Tr1 cell to CD4+ T cell ratios, the patients' Tr1 cell to FoxP3+ Treg ratios were calculated. The IL-6, IL-7, IL-10, TGF-β and IFN-γ concentration in the serum of MG patients and normal controls (NCs) were measured via ELISA. Results: We found a significantly positive correlation between the Tr1 cell/CD4+ T cell ratio and the anti-AChR Ab (r = 0.6889 ± 0.4414, p = 0.0401). Although there were no significant differences in the relationship between FoxP3+ Treg cells and anti-AChR Ab, a positive correlation between the Tr1 cell/FoxP3+ Treg cell ratio and the anti-AChR Ab (r = 0.7110 ± 0.4227, p = 0.0318) was observed. In addition, the Tr1 cell/CD4+ T cell ratio but not the proportion of FoxP3+ Tregs was positively correlated with IL-10 (p = 0.048). These results suggested that in the process of the immunomodulatory effect of Tr1 cells in patients with gMG, IL-10 and other cytokines may be involved, but the specific mechanism needs further study. Conclusion: This is the first study of the immunoregulatory mechanism of Tr1 cells in gMG. We conducted this study to elucidate the significance of Tr1 cells in the pathogenesis of MG. We believe that in patients with gMG, Tr1 cells may play an immunomodulatory role in counteracting AChR-related autoimmune responses. In this process, IL-10 and other immunomodulatory cytokines may be involved.